Monitoring the sustainable development goals at a local level: information transparency on public health (SDG 3) in Brazilian municipalities (Sustainability in Debate, 2021)
In Brazil, the process of localizing the Sustainable Development Goals (SDGs) using public databases as a reference face technical, institutional and political challenges. There are practically no comprehensive and up-to-date studies on the downscaling of the SDG indicators at the smallest territorial scales, such as the municipal one. In a context of unprecedented health emergency, such as COVID-19 pandemic, this paper discusses the capacity of the Brazilian public information system to support SDG 3’s (good health and well-being) indicators localizing at the municipal scale. The study evaluated the proposed indicators for SDG 3, as well as the databases that underpin these indicators. The results and discussion point out the main data and process deficiencies in, as well as potentials and robustness of the public health information systems at state and municipal scales in the effort of localizing the SDG 3.